Thyristor soft-starter for Mawdsley's demonsration set / Mohamad Abdullah - Abdullah, Mohamad (1997)
This thesis presents an improvement of the Mawdsley's demonstration set starter from mechanical starter to soft starter using power electronic components. DC chopper using SCR is employed as converter. Cost and the reliability are considered. The implementation of the soft-starter involved design, simulation, construction and performance validation.